2019
DOI: 10.7819/rbgn.v21i2.3977
|View full text |Cite
|
Sign up to set email alerts
|

Big bath and goodwill impairment

Abstract: Purpose -To analyze the extent to which recognition of impairments in goodwill is associated with periods of negative results before these losses (big bath practices). To determine whether indebtedness and the capital market restrict the recognition of such losses in big bath practices.Design/methodology/approach -Quantitative empirical study based on accounting and market data of companies listed on the Lisbon and Madrid stock exchanges (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), supported by mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…In a study applied to Portuguese companies, Castro (2012) cannot reach a conclusion about big bath practices, while Alves (2011Alves ( , 2013 confirms the relevance of IMP_GW as a discretionary element of accruals. Gonçalves et al (2019), who analyzed Portuguese and Spanish companies, concluded that there are big bath practices, especially in Spanish companies.…”
Section: Negative Results (Pre-impairment)mentioning
confidence: 99%
“…In a study applied to Portuguese companies, Castro (2012) cannot reach a conclusion about big bath practices, while Alves (2011Alves ( , 2013 confirms the relevance of IMP_GW as a discretionary element of accruals. Gonçalves et al (2019), who analyzed Portuguese and Spanish companies, concluded that there are big bath practices, especially in Spanish companies.…”
Section: Negative Results (Pre-impairment)mentioning
confidence: 99%
“…142 (goodwill and other intangible assets) used discretion in determining goodwill impairment and found that more leveraged firms would have lower goodwill impairment to avoid violating debt covenants. Gonçalves et al (2019) analyzed the relationship between goodwill impairment and the big bath strategy for companies with securities traded on the Lisbon and Madrid stock exchanges from 2007 to 2015. Their results suggest that the recognition of impairment losses could play an important role in big bath practices in companies with already negative current earnings.…”
Section: Determinants Of the Recognition Of Impairment Of Non-current...mentioning
confidence: 99%
“…Zang (2008) analisou se gestores das companhias que adotaram o SFAS n. 142 (goodwill and other intangible assets) utilizaram discricionariedade para determinar a perda por redução ao valor recuperável do goodwill e constatou que as empresas mais alavancadas teriam uma perda de redução do goodwill menor para evitar a violação dos covenants de dívida. Gonçalves et al (2019) analisaram a relação entre impairment de goodwill e a estratégia big bath de empresas com títulos negociados nas bolsas de Lisboa e de Madrid no período 2007 a 2015. Seus resultados apontam que o reconhecimento de perda por redução ao valor recuperável de ativos poderia assumir um papel importante em práticas de big bath em empresas com resultados correntes já negativos.…”
Section: Impairment Em Ativos Não Circulantesunclassified